Cephalometric effects of the use of 10-hour Force Theory for Class II treatment - Marise de Castro Cabrera; Carlos Alberto Gregório Cabrera; Karina Maria Salvatore de Freitas; Marcos Roberto de Freitas; Guilherme Janson; Laura de Castro Cabrera (Dental Press Editora, 2012)
OBJECTIVE: This study aimed to evaluate the cephalometric effects promoted by the orthodontic treatment of Class II malocclusion patients with the use of the 10-Hour Force Theory, that consists in the use of fixed appliances with 8 hours a day using a cervical headgear appliance and 16 hours a day using Class II elastics, 8 hours on the first mandibular molar and 8 hours in the second mandibular molar. METHODS: Sample comprised 31 patients with mean initial age of 14.90 years, final mean age of 17.25 years and mean treatment time of 2.35 years. The lateral cephalograms in pre-treatment and post-treatment stages were evaluated. Evaluation of cephalometric changes between initial and final treatment phases was performed by paired t test. RESULTS: The cases treated with the 10-Hour Force Theory presented a slight restriction of anterior displacement of the maxilla, increase in the effective length of the mandible, significant improvement of the maxillomandibular relationship, significant increase in anterior lower face height, distal tipping of the maxillary premolar crowns, extrusion and distal tipping of the roots of maxillary molars, significant proclination and protrusion of mandibular incisors, significant extrusion and mesialization of mandibular molars, besides a significant correction of the molar relationship, overjet and overbite. CONCLUSION: The use of the 10-Hour Force Theory in treatment of Class II malocclusion provided satisfactory results. OBJETIVO: esse estudo objetivou avaliar os efeitos cefalométricos promovidos pelo tratamento ortodôntico de pacientes com má oclusão de Classe II com o uso da Teoria de Força das 10 Horas, que consiste no uso de aparelho ortodôntico fixo, 8 horas diárias de uso de aparelho extrabucal cervical e 16 horas de uso de elásticos de Classe II, sendo 8 horas com apoio no primeiro molar inferior e 8 horas com apoio no segundo molar inferior. MÉTODOS: a amostra consistiu de 31 pacientes, com idade média inicial de 14,90 anos, idade média final de 17,25 anos e tempo médio de tratamento de 2,35 anos. Foram avaliadas as telerradiografias em norma lateral nas fases pré e pós-tratamento ortodôntico. Para avaliação das alterações cefalométricas entre as fases inicial e final de tratamento, foi utilizado o teste t dependente. RESULTADOS: os casos tratados com a Teoria de Força das 10 Horas apresentaram uma suave restrição do deslocamento anterior da maxila, aumento do comprimento efetivo da mandíbula, melhora significativa da relação maxilomandibular, aumento significativa da altura facial anteroinferior, inclinação para distal da coroa dos pré-molares superiores, extrusão e inclinação para distal da raiz dos molares superiores, inclinação para vestibular e protrusão significativa dos incisivos inferiores, extrusão e mesialização significativos dos molares inferiores, além de correção significativa da relação molar e dos trespasses horizontal e vertical. CONCLUSÃO: o uso da Teoria de Força das 10 Horas no tratamento da má oclusão de Classe II proporcionou resultados satisfatórios.